Risk Factors Of Sexual Patterns In Fertile Women Of Cervic Lessions - Bambang Sarwono; Pramono Giri Kriswoyo (Midwifery and Nursing Research, 2022)
Background: The incidence of cervical lesions that can progress to cervical cancer is estimated at 100 per 100,000 population. In 2013, cervical cancer was the most common cancer in Indonesia (0.8%). The incidence of cervical cancer in Magelang Regency in 2018 reached 2.3%, higher than the incidence in Central Java Province. This study aims to determine the magnitude of the risk factors for cervical lesions due to sexuality patterns in the Magelang Regency area. The purpose of this study was to determine several risk factors for the occurrence of cervical lesions and to find out what factors had the most influence on these events in Magelang Regency in 2020. By knowing the risk factors, the public knew to anticipate them. Methods: This study uses an analytical survey. The population of this study were all women who had partners of childbearing age. Samples were taken using accidental sampling, namely patients who did VIA examinations at independent practice midwives in the Magelang Regency area. Results: factors that did not affect the incidence of cervical lesions were the respondent's age, first experience of sexual intercourse (p 0.548), family planning methods (p 0.451) and genital hygiene (p 0.512). The factors that contributed to the incidence of cervical lesions were the number of sexual partners (p 0.164, OR 0.378), use of assistive devices (p 0.000, OR 8.634) and frequency of sex (p 0.000, OR 2.888) Conclusion: The biggest contributor to these factors is the use of sexual aids